Pengaruh Stres Kerja Dan Perilaku Cyberloafing Terhadap Produktivitas Perangkat Desa Se-Kecamatan Purwasari Kabupaten Karawang - Rahmayanti, Putri Anisa; Karyaningsih, Karyaningsih (Peneliti.net, 2024)
The aim of this research is to measure, test and explain the magnitude of the influence of work stress and cyberloafing behavior on the productivity of village officials in Purwasari District, Karawang Regency.To collect data, present findings, analyse and test hypotheses, and draw conclusions and recommendations, this study uses a quantitative approach using descriptive and verification analysis. This study used a non-probability sampling technique with a saturated sample method to collect data from a total of 105 participants. Likert scale analysis and path analysis, implemented in SPSS version 25, formed the basis of this data analysis method. The research results indicate that the correlation coefficient between job stress and cyberloafing behavior is -0.211, falling within the low category, displaying a negative direction, and being significant. The partial effect of work stress on the productivity of village officials in Purwasari Subdistrict, Karawang Regency is 9.4%. On the other hand, the partial effect of cyberloafing behavior on the productivity of village officials in Purwasari Subdistrict, Karawang Regency is 7.4%, signifying that job stress contributes more to village officials' productivity compared to cyberloafing behavior. The simultaneous effect of job stress and cyberloafing behavior on the productivity of village officials in Purwasari Subdistrict, Karawang Regency is 16.8%, with the remaining 83.2% being attributed to other unexamined variables.